Preparação de eletrodo contendo Poli(dimetilsiloxano) funcionalizado com grupo tiol aplicado à detecção eletroquímica de metais - Barion Filho, José Roberto (2014)
In the present work the main objective was the development of a new type of electrode from a silicon network functionalized with the thiol group. The synthesis was made through hydrolysis and condensation reactions using Poly(dimetilsiloxane) (PDMS) and the alkoxysilane 3-mercaptopropyl-trimethoxysilane (MPTS). To characterize the material were used Infrared Absorption Spectroscopy and Thermogravimetry. For the electrochemical experiments, a carbon paste electrode containing the prepared material was prepared. A composition study was made in order to obtain a new electrode with features that allow the detection of metals. The electrochemical behavior of the material was studied using Cyclic Voltammetry with potassium ferricyanide. Differential Pulse Voltammetry Technique was used for the detection tests with solutions containing cobalt, zinc, copper and cadmium, the last two were detected. Cadmium was detected in lower concentrations than copper, suggesting that interaction with the sulfur is higher with cadmium. Furthermore, the obtained values for cadmium detection in Differential Pulse Voltammetry were compared with Flame Atomic Absorption data, presenting near values.